Pengaruh Faktor Keuangan dan Non-keuangan Mencapai Keberhasilan Start-up Bisnis [Factors Influencing Financial and Non-Financial Start-up Business Success] - Sri Nathasya Br Sitepu (Universitas Pelita Harapan, 2015)
Business start-up is the term used for the many new efforts applied when business growth is fairly rapid. The success of start-up businesses can be measured by financial and non-financial factors. Financial factors are reflected in the magnitude of profits obtained by start-up business. Non-financial factors are measured from the attitudes of young entrepreneurs: self-efficacy and risk taking propensity. The business start-up community can have difficulty growing due to the lack of knowledge about measuring business success based on financial and non-financial factors. The purpose of this research is to help entrepreneurs measure the success of the start-up businesses they run. The object of the research is a start-up business that produces chips of banana at Mojowarno. This research uses a quantitative approach to process data and information research. The results of the research presents that financial and non-financial achievements affect simultaneously results.